MIRERC 069/2025: Marginal Costs, Usage Decisions, And Electric Cooking Adoption study in Nakuru County - Susanna Berkouwer; Joshua Dean; Suleiman Amanela; Mutwiri, Antony (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
EXECUTIVE SUMMARY This research proposal aims to advance clean energy access and reduce carbon emissions by improving household technology adoption in Kenya. In collaboration with BURN (a cookstove manufacturer), Busara (a local research organization), and nLine (a grid watch startup), the study will evaluate the adoption and usage of electric cookstoves among up to 3,000 individuals in Kenya. Although modern cooking technologies are available, many households continue to rely on polluting fuels such as charcoal and firewood due to high upfront costs, unreliable electricity, and limited access to subsidies. The study seeks to generate evidence on the factors influencing electric cookstove adoption. Its primary objectives are to estimate household energy expenditures and CO2 emissions, examine the determinants of stove choice, and assess demand for clean cooking solutions under varying stove payment discounts and electricity subsidy levels. The study will also include a decision-aid randomization to evaluate whether suggested calculations or prompts influence participants' ability to estimate stove usage costs. This research will aim to produce actionable insights for policymakers, energy providers, and funders working to promote energy equity, reduce environmental harm, and support the scale-up of clean cooking technologies.